Induction of beta interferon by human immunodeficiency virus type 1 and its gp120 protein in human monocytes-macrophages: role of beta interferon in restriction of virus replication. - Gessani, S (1994)
In vitro cultivated human monocytes show a time-dependent differentiation into macrophages, characterized by an increased expression of macrophage-specific antigens. Monocytes-macrophages were infected with human immunodeficiency virus type 1 strain Ba-L (HIV-1Ba-L) at different stages of differentiation. When 7-day cultured macrophages were infected in the presence of antibodies to beta interferon (IFN-beta), a significant increase in HIV-1 p24 release was detected. This effect was not observed in 1-day monocytes. This finding suggests that IFN-beta secreted by the infected macrophages inhibits p24 release. Treatment of cultured macrophages with recombinant gp120 (rgp120) protein resulted in the induction of IFN-beta mRNA and in an antiviral state to vesicular stomatitis virus. This rgp120-induced antiviral state was largely neutralized by antibodies to IFN-beta, whereas anti-IFN-alpha antibodies were ineffective. In cultured macrophages, 0.1 IU of IFN-beta per ml was sufficient to induce a marked inhibition of vesicular stomatitis virus yield, whereas this dose was ineffective in 1-day monocytes. These results indicate that (i) HIV-1 (possibly in part through its gp120 protein) induces low levels of IFN-beta in macrophages and (ii) this IFN-beta is very effective in inducing an antiviral state in differentiated macrophages.